Private Membership Test for Bloom Filters - Tommi Meskanen; Jian Liu; Sara Ramezanian; Valtteri Niemi (United States, 2025)
We study the problem of running a set membership test in private manner. We require that a client wants to have the option of not revealing the item for which the membership test is done. Respectively, the server does not wants to reveal the contents of the whole set. A Bloom filter is applied in the membership test. We present two protocols based on prior work as well as a new protocol. Each of these is having a slightly different privacy and complexity properties. We motivate the problem in the context of an anti-malware client checking application fingerprints against a cloud-based malware signature database.
Proceedings: The 9th IEEE International Conference on Big Data Science and Engineering